2023
DOI: 10.1002/cam4.6240
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a prognostic nomogram for gastrointestinal stromal tumors in the postimatinib era: A study based on the SEER database and a Chinese cohort

Abstract: BackgroundAfter the standardization, recording and follow‐up of imatinib use that significantly prolongs survival of gastrointestinal stromal tumors (GISTs), a comprehensive reassessment of the prognosis of GISTs is necessary and more conductive to treatment options.MethodsA total of 2185 GISTs between 2013 and 2016 were obtained from the Surveillance, Epidemiology, and End Results database and comprised our training (n = 1456) and internal validation cohorts (n = 729). The risk factors extracted from univaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 58 publications
0
3
1
Order By: Relevance
“…Nevertheless, previous research has indicated that the Mitotic rate did not display any significant variations in survival outcomes when undergoing multifactor feature selection. The observed disparity is incongruous with the clinical guidelines indicated earlier 7,8,10,11 . The veracity is found within the survival Cox nomograms, which incorporate the independent clinical factor Mitotic rate and the comprehensive index AJCC stage as simultaneous variables in the nomogram.…”
Section: Discussioncontrasting
confidence: 78%
See 3 more Smart Citations
“…Nevertheless, previous research has indicated that the Mitotic rate did not display any significant variations in survival outcomes when undergoing multifactor feature selection. The observed disparity is incongruous with the clinical guidelines indicated earlier 7,8,10,11 . The veracity is found within the survival Cox nomograms, which incorporate the independent clinical factor Mitotic rate and the comprehensive index AJCC stage as simultaneous variables in the nomogram.…”
Section: Discussioncontrasting
confidence: 78%
“…However, the existing literature oversimplifies the treatment of missing data classified as 'unknown' in the development of nomograms. Several research 7 , 8 , 10 , 11 consider the classification of 'unknown' as a distinct category. The validity of this assumption is frequently disregarded, as it is contingent upon the proportions of categories inside the 'unknown' group being similar to the overall proportions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations